Nuclear photoproduction of pseudoscalar mesons at forward angles up to 6.0 GeV - Rodrigues, T. E.; Arruda-Neto, J. D. T.; Mesa, J. [UNESP]; Garcia, C.; Shtejer, K.; Dale, D.; Nakagawa, I.; Cole, P. L.; Alarcon, R.; Djalali, C.; Umeres, F. (Amer Inst Physics, 2007)
The nuclear incoherent pi(0) photoproduction cross section from C-12 is evaluated at forward angles in the 4.0 to 6.0 GeV energy range using the multicollisional intranuclear cascade model MCMC. The model incorporates some improvements in comparison with previous versions associated with the momentum distribution (MD) for light nuclei - extracted from the available (e,e'p) data - as well as the evaluation of the shadowing effects during the photo-nucleus interaction. The final results of the single and double differential cross sections at forward angles are very sensitive to the MD parameterizations due to the Pauli principle, which largely suppresses the cross sections for low momentum transfer. The attenuation of the nuclear cross section due to pion - nucleus final state interactions is approximately 40% (without nuclear shadowing), which is in nice agreement with the predictions from the Glauber model. The single and double 70 differential cross sections are presented for possible applications for the interpretation of the inelastic background in the PrimEx experiment at the Jefferson Laboratory.
Keywords: meson photoproduction; intranuclear cascade model; nuclear matter; meson-nucleus final state interactions; nuclear shadowing